PELATIHAN PENGOLAHAN DATA MENGGUNAKAN SPSS DAN SMARTPLS SEBAGAI UPAYA PENINGKATAN KOMPETENSI MAHASISWA TUGAS AKHIR - Perangin-Angin, Naca (Jurnal Pengabdian Bukit Pengharapan, 2024)
The purpose of carrying out this community service activity is as an effort to improve the competence of final project students in processing research data using SPSS and SmartPLS, so that they can complete the final project on time. Based on the results of the pre test and post test of the training, it can be seen that there is a significant increase in understanding related to SPSS and SMartPLS data processing. This training is expected to improve the quality of student research, produce better scientific works, and prepare students to become independent and competent researchers in analyzing research data..